FINANCIAL REPORTING PRACTICE AS A RITUAL: UNDERSTANDING ACCOUNTING WITHIN INSTITUTIONAL FRAMEWORK - Anis Chariri (Universitas Hayam Wuruk Perbanas, 2011)
This study is aimed is to understand a ritual in financial reporting practice of a single com- pany, and how institutional theory is useful to explain such ritual through institutionalized isomorphism. Ontologically, this study is built on a belief that financial reporting practice is an institutional practice concerning the supply of information. As such, this study employed interpretive paradigm and was conducted in an insurance company, as a research setting. To improve the credibility of the research findings, the data were collected from interview, ob- servation, and document analyses which were manually analyzed using a method suggested by Marshall and Rossman (1999) and Seidel (1998). It reveals that financial reporting prac- tice has been perceived by organizational members of PT ABTBK as an institutionalized rou- tine that becomes a ritual in the company. Financial reporting practice is seen as a ritual of constructing and delivering information to an audience using “a holy guidance of ceremony” (regulations, law, standards and procedures). In doing so, the company employed three insti- tutionalized isomorphism as explained by the institutional theory. It advocates that financial reporting practice of the company is a socially-dynamic process that is not value free, but rather a socially constructed reality.